THERMO-PHYSICAL PROPERTIES OF BEESWAX (FUDMA JOURNAL OF SCIENCES, 2020)
This study presents an investigation conducted on thermo-physical properties of beeswax. Bees wax has been identified with the potentials of being used in thermal storage application, its properties were said to differ according to nesting ecology. This research investigated the thermo-physical properties of three samples of beeswax from different nesting ecology using METTLER TELODO STARe SW13.00 version differential scanning calorimetry, thermo-gravimetric analysis and differential thermal analysis. The results showed that, the melting points of sample A, B and C are 60oC, 60.01oC and 64.94oC respectively. Thermal conductivities of the samples are 3.45 W/moK, 6.69 W/moK and 1.8W/moK, latent heat of fusion of 133.32 J/g, 200.01 J/g and 66.93J/g for sample A, B and C. Hence, from the results obtained, beeswax can be used in low temperature thermal storage applications
Keywords: Ecology, Thermogram, Endothermic, Exothermic, Nesting